Tomato Cutin Deficient 1 (CD1) and putative orthologs comprise an ancient family of cutin synthase‐like (CUS) proteins that are conserved among land plants. (11th February 2014) - Yeats, Trevor H.; Huang, Wenlin; Chatterjee, Subhasish; Viart, Hélène M‐F.; Clausen, Mads H.; Stark, Ruth E.; Rose, Jocelyn K.C.
Summary The aerial epidermis of all land plants is covered with a hydrophobic cuticle that provides essential protection from desiccation, and so its evolution is believed to have been prerequisite for terrestrial colonization. A major structural component of apparently all plant cuticles is cutin, a polyester of hydroxy fatty acids; however, despite its ubiquity, the details of cutin polymeric structure and the mechanisms of its formation and remodeling are not well understood. We recently reported that cutin polymerization in tomato (Solanum lycopersicum) fruit occurs via transesterification of hydroxyacylglycerol precursors, catalyzed by the GDSL‐motif lipase/hydrolase family protein (GDSL) Cutin Deficient 1 (CD1). Here, we present additional biochemical characterization of CD1 and putative orthologs from Arabidopsis thaliana and the moss Physcomitrella patens, which represent a distinct clade of cutin synthases within the large GDSL superfamily. We demonstrate that members of this ancient and conserved family of cutin synthase‐like (CUS) proteins act as polyester synthases with negligible hydrolytic activity. Moreover, solution‐state NMR analysis indicates that CD1 catalyzes the formation of primarily linear cutin oligomeric products in vitro. These results reveal a conserved mechanism of cutin polyester synthesis in land plants, and suggest that elaborations of the linear polymer, such as branching or cross‐linking, may require additional, as yet unknown, factors.